Emotional Branding The shift in branding paradigm - Chan, Mei Yan (2004)
An extensive amount of academic papers have acknowledged that consumers’ decision making process involves not only tangible but also intangible attributes (Copeland, 1925; Sharitt, 1992; Paul & Olson, 1994; Antonides & Raaij, 1998; Aakar, 1991; Kotler, 1996; Zaltman, 2003) However, the power of emotion has been largely neglected by most companies in the past few decades. Recently, as some practitioners recognised the shift of economy and increasing expectation derived from consumers, the branding focus has shifted from product-oriented to emotion oriented. This research aims to illustrate the branding in a high involvement, complex decision making process in the property market in Hong Kong. It provides a guideline for future research to be conducted on different level of purchase involvement in order to compare the different degree of emotional branding impact in connecting consumers with the brands. As such, the focus of the research process was directed atadvertisements.Findings revealed that marketers are practicing emotional branding with an increasingly use of emotional attributes in the advertising message. The research from the consumer perspective to evaluate the effect of emotional value receives an encouraging response; corresponding to the literature finding that the market is increasingly emphasis on emotional and symbolic value.